Associations among the food environment diet quality and weight status in Cree children in Québec ... - Raine, Kim D.; Willows, Noreen D.; Marshall, Dru; McCargar, Linda J.; Arnold, Amber; Downs, Shauna M. (University of Alberta Library, 2009)
To explore the relationship among children’s diet quality, weight status and food environment in subarctic Canada. In the cross-sectional study, children’s BMI was calculated, diet quality was assessed using three 24 h dietary recalls and children were asked about their home food environment and source of meals. Two Aboriginal Cree communities in northern Québec. Two hundred and one children in grades 4–6. The majority (64·2 %) of children were overweight (29·9 %) or obese (34·3 %). Weight status was not associated with reported restaurant meal frequency or the home food environment. The 18 % of children who consumed three or more restaurant meals in the three days of recall consumed, on average, 2004 kJ (479 kcal) more energy daily than children consuming no restaurant meals and had higher intakes of fat, saturated fat, Ca and soda. Most foods contributing to energy and dietary fat were energy-dense market foods of low nutritional value such as sweetened beverages and snack foods. Only 68 % of children ...